Styrian refining at Ipanema Ironworks: gestures engendering crystals in 1885 - Landgraf, Fernando Jose Gomes; Paulo Eduardo Martins (Khronos, 2022)
The production of wrought iron bars at Ipanema Ironworks is examined based on the description written by Dupré, in 1884, about the refining process used there, and by the microstructural analysis of samples obtained in the collections of Museu Nacional, in Rio de Janeiro, in 2014. Similar bars were used in the Brazilian railroads of the 19 Century. The microstructural inhomogeneities observed in those bars are similar to those described in the international literature about contemporary pieces. It is possible to correlate the chemical composition of the iron ore used at Ipanema to the composition of crystals found in the slag inclusions, becoming a viable parameter to establish a “chemical signature” of the bars there made.